2016
DOI: 10.1038/mt.2016.2
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Small Single-domain Antibody That Effectively Inhibits Matrix Metalloproteinase 8

Abstract: A detrimental role for matrix metalloproteinase 8 (MMP8) has been identified in several pathological conditions, e.g., lethal hepatitis and the systemic inflammatory response syndrome. Since matrix MMP8-deficient mice are protected in the above-mentioned diseases, specific MMP8 inhibitors could be of clinical value. However, targeting a specific matrix metalloproteinase remains challenging due to the strong structural homology of matrix metalloproteinases, which form a family of 25 members in mammals. Single-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 64 publications
2
11
0
Order By: Relevance
“…We demonstrated that by panning with FliC, we could extract a sdAb, Abi-Se07, with a K D of 16.2 nM, within the mid-nM to high-pM range for sdAbs as reported by others (Muyldermans and Lauwereys, 1999; Demeestere et al, 2016; Sulea et al, 2018). Abi-Se07 contains a longer than average CDR3 loop (Figure 1), and could suggest that its CDR3 forms a convex paratope to access a cryptic epitope on FliC as observed with other long CDR3 sdAbs (Stijlemans et al, 2004; De Genst et al, 2006; Schmitz et al, 2013).…”
Section: Discussionsupporting
confidence: 74%
“…We demonstrated that by panning with FliC, we could extract a sdAb, Abi-Se07, with a K D of 16.2 nM, within the mid-nM to high-pM range for sdAbs as reported by others (Muyldermans and Lauwereys, 1999; Demeestere et al, 2016; Sulea et al, 2018). Abi-Se07 contains a longer than average CDR3 loop (Figure 1), and could suggest that its CDR3 forms a convex paratope to access a cryptic epitope on FliC as observed with other long CDR3 sdAbs (Stijlemans et al, 2004; De Genst et al, 2006; Schmitz et al, 2013).…”
Section: Discussionsupporting
confidence: 74%
“…EtOH treatment also increased MMP-1 and MMP-3; both have been involved in extracellular matrix disruption surrounding the RPE and the Bruch's membrane [20,31,57]. The increase in MMP-8 also corroborates the activation of the inflammation process in RPE under EtOH exposure [58].…”
Section: Discussionmentioning
confidence: 83%
“…High serum or plasma levels of MMP-8 correlate to sepsis severity and fatality 39,40. Protection from endotoxin shock following LPS challenge was observed in mice treated with peptidic inhibitors of MMP-8 and MMP-9, and an MMP-8 selective nanobody 7779. MMP-8 has been indicated to be a key mediator in the regulation of innate immunity 80.…”
Section: Discussionmentioning
confidence: 99%